Recombination of mannanase gene man23 and its expression in Brevibacillus brevis - ZHOU Hai-yan; RAO Li-qun; WU Yong-yao (浙江大学学报. 农业与生命科学版, 2008)
To promote the production of mannanase (Man23) and reduce its degradation in vitro, the man23 gene was ligated with a high-expression vector pHY-p43. The recombinant plasmid pHY-p43-man23 was transformed into Brevibacillus brevis. The man23 gene regulated by the strong promoter p43 produced mannanase activity of 22480 U·mL-1, which was 26.7% higher than original strain Bacillus subtilis B23. Because B. brevis is a protease-defective strain, SDS-PAGE of the extracellular protein from B. brevis showed a much stronger band of the target protein and week or little non-target protein bands. This efficient and economic system can produce correctly folded extracellular mannanase with much higher yield and activity. The expression profile indicated that B. brevis was a perfect host cell for gene engineering.